Hubungan Antara Perilaku Hidup Bersih dan Sehat (PHBS) dengan Kejadian Diare Pada Balita - Yuni Kristin Hasibuan, Hotma; P Marpaung, Alexander; Simanjuntak, Maestro (Jurnal Kedokteran Methodist, 2021)
Background: Diarrhea is a condition of excreting feces or feces with an increasing frequency (three times in 24 hours). This case is of particular concern to under-fives because it has become the second most common case that results in 1.7 billion deaths every year and most of the factors are influenced by the hygiene behavior of mothers and toddlers. The purpose of this study was to determine the correlation of clean and healthy living behavior (PHBS) with the incidence of diarrhea in toddlers Method : This study uses a systematic literature review or library research, using secondary data using Indonesian. The sample used is toddlers. Data is collected by summarizing and critically reviewing each journal, where each journal can use cross-sectional, cohort, case-control studies, and logistic regression tests Results : There is a significant relationship between Clean and Healthy Living Behavior (PHBS) and the incidence of diarrhea in toodler where the characteristics in this study are hand washing, use of healthy latrines, use of clean water, and waste disposal. Conclusion: There is a relationship between Clean and Healthy Life Behavior (PHBS) with Diarrhea in Toddlers.